(untitled) (Innovative Technologica: Methodical Research Journal, 2024)
Reinforcement is a method of strengthening a material and increasing its load-bearing properties with another building material, which has higher strength indicators relative to the base material [3]. This method is used in the manufacture of reinforced concrete and stone structures. The purpose of reinforcement is to increase the load-bearing capacity of the structure and reduce the likelihood of cracks caused by temperature changes. For this purpose, materials with increased strength characteristics, such as steel, are used. It is important to understand what reinforcement is in order to correctly apply it in construction and ensure the reliability of structures [2].